ANALISIS HAK KEPEMILIKAN LAHAN PERKEBUNAN KELAPA SAWIT DI DESA SETABU DAN DESA LIANG BUNYU KECAMATAN SEBATIK BARAT KABUPATEN NUNUKAN - Deby Ayu Herlin; Adi Sutrisno (J-PEN Borneo : Jurnal Ilmu Pertanian, 2019)
ABSTRACT While the research objectives formulated based on the background are: (1) to know the ownership rights of plantation land based on legislation in laws in the Republic of Indonesia; (2) to know the facts of land ownership rights of oil palm plantations in Setabu Village and Liang Bunyu Village, West Sebatik District, Nunukan Regency; and (3) to know the suitability of the land ownership rights stated in the laws and regulations with the ownership facts in Setabu and Liang Bunyu Villages in West Sebatik District, Nunukan Regency. The data used consists of secondary data and primary data, collected using document study techniques and interviews using questionnaires. The data obtained are then analyzed using qualitative content analysis techniques and qualitative descriptive analysis. The results of this study are (1) plantation land ownership rights based on laws and regulations consisting of ownership rights, use rights, business use rights and customary rights, where ownership rights are the most fulfilled and strongest rights: (2) plantation land rights over land controlled by farmers in Setabu Village and Liang Bunyu Village are "Right of Ownership" with proof of title in the form of Certificate, Letter of Village Head (SPPT) and Sub-District Letter (SPPH); and (3) the plantation ownership rights included in the legislation and the ownership rights to the plantation land controlled by the farmers of Setabu Village and Liang Bunyu Village are in conformity, namely the ownership of plantation land in the form of " Ownership Rights ", but evidence of plantation ownership rights in the two villages are more in the form of a Village Head Letter (SPPT) and Sub-District Letter (SPPH). Keywords: Property rights, legislationABSTRAK Sedangkan tujuan penelitian yang dirumuskan berdasarkan latar belakang adalah: (1) untuk mengetahui hak kepemilikan lahan perkebunan berdasarkan peraturan perundang-undangan di Republik Indonesia; (2) untuk mengetahui fakta hak kepemilikan lahan perkebunan kelapa sawit di Desa Setabu dan Desa Liang Bunyu, Kecamatan Sebatik Barat, Kabupaten Nunukan; dan (3) untuk mengetahui kesesuaian hak kepemilikan tanah yang dinyatakan dalam undang-undang dan peraturan dengan fakta kepemilikan di Desa Setabu dan Liang Bunyu di Kecamatan Sebatik Barat, Kabupaten Nunukan. Data yang digunakan terdiri dari data sekunder dan data primer, dikumpulkan menggunakan teknik studi dokumen dan wawancara menggunakan kuesioner. Data yang diperoleh kemudian dianalisis dengan menggunakan teknik analisis isi kualitatif dan analisis deskriptif kualitatif. Hasil dari penelitian ini adalah (1) hak kepemilikan tanah perkebunan berdasarkan hukum dan peraturan yang terdiri dari hak kepemilikan, hak pakai, hak pakai bisnis dan hak ulayat, di mana hak kepemilikan adalah hak yang paling terpenuhi dan terkuat: (2) hak atas tanah perkebunan atas tanah yang dikuasai oleh petani di Desa Setabu dan Desa Liang Bunyu adalah "Hak Kepemilikan" dengan bukti kepemilikan dalam bentuk Sertifikat, Surat Kepala Desa (SPPT) dan Surat Kecamatan (SPPH); dan (3) hak kepemilikan perkebunan yang termasuk dalam undang-undang dan hak kepemilikan atas tanah perkebunan yang dikendalikan oleh petani Desa Setabu dan Desa Liang Bunyu sudah sesuai, yaitu kepemilikan tanah perkebunan dalam bentuk "Hak Kepemilikan", namun bukti hak kepemilikan perkebunan di kedua desa tersebut lebih berupa Surat Kepala Desa (SPPT) dan Surat Camat (SPPH). Kata kunci: Hak properti, undang-undang